Penerapan Model Pembelajaran Two Stay Two Stray Untuk Meningkatkan Keterampilan Diskusi Siswa Kelas X-IPA1 di SMAN 5 Kota Ternate Tahun pelajaran 2021-2022 - Difa Fara; Alimuddin Alimuddin (EDUKASI, 2023)
This study aims to improve the discussion skills of class X-IPA1 students of SMA Negeri 5 Kota Ternate, through the two stay two stray learning model. The research focused on problems related to the low skills of students in discussion activities including aspects of courage and fluency in speaking. This type of research is classroom action research with three cycles, each cycle consisting of: planning, implementing, observing and reflecting. Data collection techniques and tools in this study used descriptive analysis techniques for data in the form of observation sheets, interviews and observations. This research was conducted in July-August 2022. The subjects in this study were students in class X-IPA 1 at SMA Negeri 5 Kota Ternate. Data were analyzed with qualitative descriptive techniques. The results showed that the discussion skills in the aspects of courage and fluency increased in each cycle. In cycle 1 the average value on the aspect of courage is 28.13. The pre-cycle value was 77.50 in cycle I, increased to 80.63 in cycle II, and increased to 98.13 in cycle III. The aspect of speaking fluency increased with the pre-cycle average value of 25.63 to 68.75 in cycle I. The average value of cycle I increased to 80.00 in cycle II and the average value of cycle II increased to 96.25 in cycle III. Students are more skilled in discussions by applying the Two Stay two Stray learning model to the material of the text of the observation report.